2022
DOI: 10.1111/andr.13281
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of semen analysis parameter improvement after varicocoelectomy using 1 H NMR‐based metabonomics assays

Abstract: Background Varicocoele is the most common correctable cause of male infertility; however, predicting varicocoelectomy outcomes is difficult. “Omics” techniques have been increasingly used to develop new diagnostic and prognostics tools for several male infertility causes, and could be applied to study varicocoele. Objectives The objective is to create metabolomics models capable of segregating men who improved semen analysis (SA) parameters or achieved natural pregnancy after microsurgical varicocoelectomy (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Furthermore, the interest 2 of 14 in understanding the sperm physiology underlying semen quality has led to the analysis of the endogenous metabolome in healthy donor samples as well [17][18][19][20]. In addition, recent investigations have shown that a metabolomic approach is helpful for the advancement of precision medicine, since it may be used as a prognosis tool to accurately predict the efficacy of a potential treatment (e.g., varicocelectomy or microTESE) for several male infertility causes [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the interest 2 of 14 in understanding the sperm physiology underlying semen quality has led to the analysis of the endogenous metabolome in healthy donor samples as well [17][18][19][20]. In addition, recent investigations have shown that a metabolomic approach is helpful for the advancement of precision medicine, since it may be used as a prognosis tool to accurately predict the efficacy of a potential treatment (e.g., varicocelectomy or microTESE) for several male infertility causes [21,22].…”
Section: Introductionmentioning
confidence: 99%